EXTENSIONIST EXPERIENCE THROUGH THE MONITOR OF A SOCIAL GASTRONOMY COURSE (Citizenship in Action: Extension and Culture Magazine, 2025)
This article is an experience report from the perspective of a student working for the first time as a monitor in an extension activity, in a Salty Snacks Course offered by the Social Gastronomy Extension Program in Jardim da Gente of the Federal University of Ceará (GS-UFC) and the School of Self-Sustainable Gastronomy (EGA) of the Mental Health Movement (MSM). This is a descriptive study based on observations and on-site participation, using a critical, reflective, qualitative and descriptive approach to the aforementioned course. The report is based on a student of the Bachelor's degree in Gastronomy at UFC and a scholarship holder of the GS-UFC extension program, who worked as a monitor with the teachers of the aforementioned course, observing mainly the classroom teaching and the practices carried out by them. As a result, information about the Salty Snacks Course was presented, contextualizing it, focusing on the target audience (the community of Grande Bom Jardim in Fortaleza/CE), the location (EGA) and the content taught. The main occurrences were also described, mainly regarding classroom activities as perceived by the GS-UFC monitor, through the organization and monitoring of classes. Finally, the report considered it to be a gateway to teaching by providing communication skills and culinary techniques, both essential for a career in gastronomy teaching. Based on the experience, it was concluded that the learning acquired went beyond expectations because it allowed contact with the course participants and with the assisted reality, an important fact that is not found in books. In addition, it allowed awakening the desire to pursue a teaching career.
Keywords: Gastronomy; Extension; Teaching; Practice